Increased mitochondrial ROS formation by acetaminophen in human hepatic cells is associated with gene expression changes suggesting disruption of the mitochondrial electron transport chain. Issue 2 (16th April 2015) - Jiang, Jian; Briedé, Jacob J.; Jennen, Danyel G.J.; Van Summeren, Anke; Saritas-Brauers, Karen; Schaart, Gert; Kleinjans, Jos C.S.; de Kok, Theo M.C.M.
Highlights Toxic doses of acetaminophen (APAP) boost the formation of mitochondrial reactive oxygen species (ROS). Toxic doses of APAP disrupt the expression of many genes encoding the subunits of electron transport chain (ETC) complexes, and reduce the expression of SOD2, a mitochondria-specific antioxidant enzyme. Toxic doses of APAP reduce the ATP yield of human liver cells.